2021
DOI: 10.25176/rfmh.v22i1.4060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two resistance exercise programs on the health-related fitness of obese women with pain symptoms in the knees

Abstract: Introduction: Overweight negatively impacts the cardiovascular system and osteomyoarticular, promoting pain in the joints of the lower limbs. Therefore, strategies have been applied to reduce overweight through lifestyle changes. Objective: to investigate the effects of two multidisciplinary intervention programs on the health-related physical fitness of obese women with pain symptoms in the knees. Methods: Women between 40 and 59 years of age with obesity (n=59) were evaluated in the pre- and post-interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Specifically, the upper and lower-body strength assessed with different procedures (e.g., one repetition maximum in vertical chest press, one repetition maximum in supinated lat pull-down, one repetition maximum in arm press, isometric handgrip strength test, one repetition maximum in horizontal leg press, one repetition maximum in seated leg extension, one repetition maximum in leg curl, sit to stand test, standing long jump test, isometric knee extensor test, isometric ankle plantar-flexors and dorsi-flexor test) showed positive changes in individuals with obesity in favor to an INT approach [ 33 , 37 , 38 , 40 , 42 ]. Two studies [ 34 , 48 ] found similar improvements overtime without differences between training interventions (INT protocol versus control) for both upper and lower-body segments. On one hand, it could be speculated that these controversial results might be due to a reduced adherence to the training program, or to the equipment used (e.g., elastic bands, dumbbells, suspension belts, kettlebells, medicine balls, battle ropes), but on the other hand the duration of each training program (e.g., from eight weeks to ten months) induced a better movement pattern learning and muscle recruitment leading to positive changes in muscular strength [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Specifically, the upper and lower-body strength assessed with different procedures (e.g., one repetition maximum in vertical chest press, one repetition maximum in supinated lat pull-down, one repetition maximum in arm press, isometric handgrip strength test, one repetition maximum in horizontal leg press, one repetition maximum in seated leg extension, one repetition maximum in leg curl, sit to stand test, standing long jump test, isometric knee extensor test, isometric ankle plantar-flexors and dorsi-flexor test) showed positive changes in individuals with obesity in favor to an INT approach [ 33 , 37 , 38 , 40 , 42 ]. Two studies [ 34 , 48 ] found similar improvements overtime without differences between training interventions (INT protocol versus control) for both upper and lower-body segments. On one hand, it could be speculated that these controversial results might be due to a reduced adherence to the training program, or to the equipment used (e.g., elastic bands, dumbbells, suspension belts, kettlebells, medicine balls, battle ropes), but on the other hand the duration of each training program (e.g., from eight weeks to ten months) induced a better movement pattern learning and muscle recruitment leading to positive changes in muscular strength [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 95%
“…Cardiorespiratory fitness was investigated in six studies [ 33 , 34 , 37 , 41 , 45 , 48 ] reporting significant improvements following a specific neuromuscular training protocol. Batrakoulis and colleagues (2018) showed positive changes in VO2 max from baseline (26.1 ± 4.4 mL/kg/min) to post-training (33.1 ± 4.8 mL/kg/min; p < 0.001) following a INT protocol (e.g., high-intensity whole-body multi-joint movements in a circuit training modality respecting a heart rate maximum major of 65%) with a concomitant significant reduction in blood lactate concentration during the entire training phase (i.e., from week one to week forty) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations